Pedagogical Evaluation and Recommendations on Software Design for English Intonation Learning - Nawel Bengrait (Universitas Muhammadiyah Barru, 2021)
Learning prosody with the integration of computer technologies, mainly speech processing, gained interest among Foreign Language (FL) learners and teachers. The present paper aims at (i) evaluating different set of speech technologies that were used by the researcher in English Foreign Language (EFL) classroom during courses of phonetics, and (ii) providing pedagogical suggestions on how to design software for the teaching and learning of English intonation that suits Algerian non-native speakers’ needs. The adopted approach is qualitative in nature that employs observation of the pronunciation software based on checklist criteria. The materials include Pronunciation Power, Rosetta stone, Better Accent Tutor, RTPitch, Speech Analyzer, and Praat. In light of this, the results exhibit the pros and cons of each speech program and recommendations are proposed on the criteria to select Computer Assisted Language Learning (CALL) devices for teaching English intonation. The findings revealed that Pronunciation Power and Rosetta stone focus more on the teaching of English segmental over prosodic features except for Better Accent Tutor that stresses the learning of intonation. Other speech tools as Speech Analyzer, Praat, and RTPitch provide automatic audio-visual assessment of intonational patterns and measurement of pitch and intensity values. As a result, more focus is to be given to the teaching of discourse intonation and developing materials with the employment of technological tools in order to supplement textbook instructions, and what the teacher and learner should be aware of when teaching and learning English intonation.